Kebijakan DPRK Gayo Lues Tentang Reformasi Birokrasi di Lingkup Pemerintah Gayo Lues: Studi Kasus DPRK Kabupaten Gayo Lues - Mawan Arris Andika; Junaidi Junaidi; Farhan Indra (Polyscopia, 2024)
To realize optimal bureaucratic reform, institutions are needed that have integrity in supervising and supporting government performance, especially in district/city areas, namely the people's representative council. regional (DPRD). The author as a researcher chose qualitative descriptive research to explore the research object. This research shows that the Gayo Lues Regency Government is actively implementing a number of policies to advance the region. The policy focus covers various aspects such as infrastructure development, the policies implemented in Gayo Lues Regency are clearly related to and in line with local laws and regulations. The main goal is to increase the efficiency and transparency of public services. Implementation of reforms includes organizational restructuring, increasing human resource capacity, simplifying administrative processes, and applying information technology. The principles of clean government and good governance are the foundation, with a focus on eradicating corruption and improving the quality of government.